Physiology of Elasmobranch Fishes : Structure and Interaction with Environment - Shadwick, Robert Edward, 1953-; Farrell, Anthony Peter, 1952-; Brauner, Colin J.; ScienceDirect eBooks (Amsterdam : Elsevier, 2016)
Fish Physiology: Physiology of Elasmobranch Fishes, Volume 34A is a useful reference for fish physiologists, biologists, ecologists, and conservation biologists. Following an increase in research on elasmobranchs due to the plight of sharks in today's oceans, this volume compares elasmobranchs to other groups of fish, highlights areas of interest for future research, and offers perspective on future problems. Covering measurements and lab-and-field based studies of large pelagic sharks, this volume is a natural addition to the renowned Fish Physiology series.
Text in English.
Online resource; title from PDF title page (EBSCO, viewed November 25, 2015)
Includes bibliographical references and index.
Elsevier
Keywords: Chondrichthyes -- Physiology; Fishes -- Physiology; NATURE / Animals / Fish; SCIENCE / Life Sciences / Zoology / Ichthyology & Herpetology; Chondrichthyes -- Physiology; Fishes -- Physiology; Electronic books